China's Overt Economic Rise and Latent Human Capital Investment: Achieving Milestones and Competing for the Top - Amelie F. Constant; Bienvenue Tien; Klaus F. Zimmermann; Jingzhou Meng (Institute for the Study of Labor (IZA), 2010)
We provide an overview of China's economic rise through time. Over the past decade, China has maintained 10% growth in GDP, albeit with a GDP per capita at the low level of a developing country. Its tremendous economic development has overlooked the growing social inequalities and rising resentments of the cheap workers and those laid off. The main contributor to its ascension is international trade and investment in physical capital, often at the expense of the environment. The year 1978 was the landmark for the foundation of the Chinese modern higher education system. Since then the number of students enrolled in Chinese higher education institutions has increased dramatically; China is producing serious scholars and a tremendous amount of scholarly output; more and more Chinese students seek higher education abroad; and international students find a rising interest in receiving education in China.
Keywords: F22; J24; N35; O15; O24; O53; 330; China; human capital; brain drain; higher education; Wirtschaftswachstum; Internationale Wirtschaft; Bildungsinvestition; Hochschule; Brain Drain; Auslandsaufenthalt; China